THE DEIFICATION OF THE KUSHAN RULERS (World Bulletin of Education and Learning, 2025)
The article explores the divine legitimization of the Kushan rulers, focusing on their political and ideological structures through a multi-source approach involving historical, epigraphic, numismatic, and art historical evidence. It highlights the complexity of reconstructing Kushan history due to scarce and scattered sources but stresses the importance of available materials for understanding the empire's governance and religious ideology. The study analyzes the "saptanga" model of governance, a seven-element framework from ancient Indian political thought, as applied in Kushan statecraft. It examines the hierarchical roles of the king (Svami), ministers (Amatya), people and territories (Janapada), fortresses (Durga), treasury (Kosa), military power (Bala), and allies (Mitra). The article also elucidates how Kushan kings legitimized their authority by adopting divine titles such as "Devaputra" ("Son of God") and employing religious symbolism on coins and monuments, illustrating a synthesis of Hindu-Buddhist and transregional (Chinese and Iranian) influences. This legitimization was less reliant on grand Vedic sacrifices and more on iconography and numismatic imagery, reflecting the Kushan adaptation of the cosmic order concept (Rita) and their political-theological ideology.
Keywords: Kushan empire; divine kingship; saptanga model; Numismatics; epigraphy; political Ideology; devaputra; cosmic order (Rita); hindu-buddhist syncretism; transregional influence.